Sub-Watershed Prioritization for Sustainable Sediment Management in the Upper Cisokan Hydropower Catchment Using SWAT+ - Pusparinda, Laella; Mariana Marselina (Research and Social Study Institute, 2025)
Background: Sedimentation poses a critical threat to hydropower sustainability, particularly in pumped storage systems such as the Upper Cisokan Pumped Storage (UCPS) plant in West Java, Indonesia.Aims and Methods: This study assesses the spatio-temporal dynamics of sediment yield in the Cisokan Watershed using the SWAT+ model, incorporating historical simulations (2013 and 2023) and a 2038 projection under a Business-As-Usual (BAU) scenario developed through supervised classification in Google Earth Engine (GEE).Result: Model calibration based on observed discharge data yielded satisfactory results (NSE = 0.80 in 2013, 0.65 in 2023), validating its suitability for sediment analysis. Results reveal a nearly fourfold increase in average sediment yield from 0.61 to 2.25 tons/ha/year between 2013 and 2023, with a projected rise to 5.57 tons/ha/year by 2038. A composite prioritization index, integrating current sediment output, decadal change, and sub-watershed area, identified SW-23, SW-16, and SW-5 as the highest priority areas for erosion mitigation. These findings were validated against future projections, confirming their persistent erosion risk. The study emphasizes the importance of scenario-based watershed planning in safeguarding hydropower infrastructure. By integrating sediment modeling with scenario-based land use projection via supervised classification in Google Earth Engine (GEE), this study provides a replicable framework for proactive watershed management and hydropower sustainability planning.